Pretrial detention and its interpretation in the context of potential environmental justice based on substantialist, proceduralist, and mixed criteria - Junchaya-Vera, Frecia Cristel (2024)
The objective of the study was to describe the frequency of preventive detention criteria and their interpretation concerning potential environmental justice from substantialist, proceduralist, and mixed criteria perspectives. The study, with a quantitative approach, analyzed 120 preventive detention cases in the Superior Court of Justice of Cañete (2016-2017), Lima, Peru using a structured questionnaire and SPSS v25 for data analysis. The results indicated that 58.3% of cases applied substantialist criteria, prioritizing the severity of the crime, while 25% applied proceduralist criteria, and 16.7% used mixed criteria. Although substantialist criteria ensure environmental protection, they could compromise rights such as the presumption of innocence. In the discussion, it is highlighted that the predominance of these criteria could affect the fairness of the judicial system, suggesting that a balance with proceduralist criteria, as seen in other jurisdictions, improves justice. It is concluded that judicial practices must be reviewed, operators trained, and guidelines established that promote proportionality and respect for fundamental rights.